2015
DOI: 10.1038/ng.3395
|View full text |Cite
|
Sign up to set email alerts
|

Class II HLA interactions modulate genetic risk for multiple sclerosis

Abstract: Association studies have greatly refined the understanding of how variation within the human leukocyte antigen (HLA) genes influences risk of multiple sclerosis. However, the extent to which major effects are modulated by interactions is poorly characterized. We analyzed high-density SNP data on 17,465 cases and 30,385 controls from 11 cohorts of European ancestry, in combination with imputation of classical HLA alleles, to build a high-resolution map of HLA genetic risk and assess the evidence for interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(176 citation statements)
references
References 36 publications
(55 reference statements)
8
163
0
Order By: Relevance
“…This resulted not only in the description of multiple class II HLA‐DRB1 and HLA‐DRQ1 classical alleles imputed from SNP genotypes, but also epistatic interactions between HLA‐DQA1*01:01 and HLA‐DRB1*15:01 and between HLA‐DQB1*03:01 and HLA‐DQB1*03:02. These results raise certain functional questions, for example why the protective effect of HLA‐DQA1*01:01 only manifests in the presence of the HLA‐DRB1*15:01 risk allele 50, 51. Several variants outside the classical regions of the MHC (both class I and class II) were also shown to be independently associated, suggesting biological functions beyond antigen display underlie the MHC risk effects.…”
Section: The Role Of the Mhcmentioning
confidence: 98%
See 1 more Smart Citation
“…This resulted not only in the description of multiple class II HLA‐DRB1 and HLA‐DRQ1 classical alleles imputed from SNP genotypes, but also epistatic interactions between HLA‐DQA1*01:01 and HLA‐DRB1*15:01 and between HLA‐DQB1*03:01 and HLA‐DQB1*03:02. These results raise certain functional questions, for example why the protective effect of HLA‐DQA1*01:01 only manifests in the presence of the HLA‐DRB1*15:01 risk allele 50, 51. Several variants outside the classical regions of the MHC (both class I and class II) were also shown to be independently associated, suggesting biological functions beyond antigen display underlie the MHC risk effects.…”
Section: The Role Of the Mhcmentioning
confidence: 98%
“…Beyond single‐marker analyses, in 2015 the IMSGC described a comprehensive dissection of allelic association in the broader MHC, based on over 48 000 samples with dense genotyping information through the region 50. This resulted not only in the description of multiple class II HLA‐DRB1 and HLA‐DRQ1 classical alleles imputed from SNP genotypes, but also epistatic interactions between HLA‐DQA1*01:01 and HLA‐DRB1*15:01 and between HLA‐DQB1*03:01 and HLA‐DQB1*03:02.…”
Section: The Role Of the Mhcmentioning
confidence: 99%
“…Of note, genetic predisposition can only explain a fraction of the increased susceptibility risk 44, 45. Genetic studies identified roughly about 200 genetic risk loci involved in MS susceptibility, mostly genes involved in the innate and adaptive immune responses 46, 47, 48. A recent study on genetic and epigenetic fine mapping of causal variants in several autoimmune diseases revealed the cell types most likely to contribute to MS by showing that causal variants of MS are enriched in  cis ‐regulatory elements mostly in immune cells, particularly T reg cells, T H cells, and B cells 49…”
Section: Genetic and Environmental Risk Factorsmentioning
confidence: 99%
“…Using GWAS single-nucleotide polymorphism (SNP) data (5091 cases/9595 controls), the International Multiple Sclerosis Genetics Consortium (IMSGC) reported in 2013 the isolation of 11 statistically independent effects in the MHC region: six HLA-DRB1 and one HLA-DPB1 alleles in the centromeric class II region of the locus; one HLA-A and two HLA-B alleles in the telomeric class I region; and one in the class III region between MHC class I polypeptide-related sequence B (MICB) and leukocyte-specific transcript 1 (LST1) (16 (17). Larger ongoing studies hold the potential for discovering additional independent and interactive effects.…”
Section: The Human Leukocyte Antigen Locus In Msmentioning
confidence: 99%